Myeloid differentiation protein 2 induced retinal ischemia reperfusion injury via upregulation of ROS through a TLR4-NOX4 pathway. (5th January 2018) - Chen, Huaicheng; Song, Zongming; Ying, Shilong; Yang, Xi; Wu, Wei; Tan, Qiufan; Ju, Xin; Wu, Wencan; Zhang, Xin; Qu, Jia; Wang, Yi
Highlights: ROS is a key pathological event in retinal I/R injury. MD2/TLR4 signaling pathway is involved in oxidative damage in the retina I/R. MD2 is required for the formation of TLR4/NOX4 complex. Targeting MD2 is a potential therapeutic approach in various ophthalmic diseases. Abstract: Retinal ischemia reperfusion (I/R) injury is common in many ophthalmic diseases. Recent studies have shown that toll-like receptor 4 (TLR4) is involved in ischemic retinal injury. Activation of TLRs requires specific accessory proteins such as myeloid differentiation protein 2 (MD2), which facilitate in ligand responsiveness. Therefore, inhibiting MD2 may be a novel approach to modulate TLR4 signaling and deleterious downstream effects in ischemic retinal injury. We used human Müller MIO-M1 cells treated with tert-butyl hydroperoxide (TBHP) to establish an in vitro I/R model of oxidative injury and tested the therapeutic effect of inhibiting MD2. Furthermore, we inhibited MD2 in a mouse model of retinal I/R injury and confirmed the results using MD2 knockout mice. Our studies show that pharmacological inhibition of MD2 prevented TBHP-induced reactive oxygen species (ROS) generation, inflammation and subsequent apoptosis in Müller cells. We also show that retinal I/R injury in mice induced functional deficits, increased ROS levels, inflammation and apoptosis. These pathological changes were not observed in MD2 knockout mice and attenuated when MD2 was inhibited in wildtype mice. In addition, we discovered that the mechanism of these therapeutic effects involved regulation of NADPH oxidase 4 (NOX4)-MD2-TLR4 complex formation. This study provides evidence that MD2 plays a key role in the pathogenesis of retinal I/R damage by participating in TLR4-NOX4 complex formation and elaboration of oxidative and inflammatory damage. Hence, inhibition of MD2 may reduce TLR-dependent damage during retinal I/R injury.